Refinement of anomalous dispersion correction parameters in single-crystal structure determinations. (2022) - Meurer, Florian; Dolomanov, Oleg V.; Hennig, Christoph; Peyerimhoff, Norbert; Kleemiss, Florian; Puschmann, Horst; Bodensteiner, Michael
No abstract available